Mediating Effects of Avatar Realism on Motivation in Game Based Learning - Review - Kogilathah Segaran; Ahmad Zamzuri Mohamad Ali; Wee Hoe Tan (Online Journal for TVET Practitioners, 2019)
Abstract: Virtual environments and digital games are being increasingly used as educational tools in current education settings. For the past few decades there were tremendous amount of studies involving digital game based learning (DGBL) in many subject matters to identify best design approach to increase its effectiveness. DGBL have been expanded in several ways by referring to digital entertainment games such as in using avatar which would assist the students to revise and learn on their own. Usage of avatars as an educator in the virtual learning environment is increasing as its importance increases where interactivity, learner engagement, cultural factors, communication, embodiment and motivation are crucial design considerations in a virtual learning environment. Nevertheless, question arises as what type of avatar whould be preferred by the learners in DGBL. There were dearth studies conducted on how the realism level of an avatar in DGBL would influence the emotions of a learner since researchers stated that emotions practiced throughout a learning method offer clues not solely to the effectiveness of a learning activity however additionally to the method of learning. Likewise, there were scarcity in identifying the relationship between level of realism with different elements of emotions (valence and arousal) and different theories of motivation. Thus, this paper, critically reviews the literature related to usage of avatar in DGBL. This paper also discusses the finding related to motivation and emotion factors in DGBL, relation between realism in avatar and emotion, relation between motivation, emotion and realism of avatar in DGBL.